Young Children's Mathematical Learning From Intelligent Characters. Issue 5 (20th November 2019) - Calvert, Sandra L.; Putnam, Marisa M.; Aguiar, Naomi R.; Ryan, Rebecca M.; Wright, Charlotte A.; Liu, Yi Hui Angella; Barba, Evan
Abstract : Children's math learning ( N  = 217; M age  = 4.87 years; 63% European American, 96% college‐educated families) from an intelligent character game was examined via social meaningfulness (parasocial relationships [PSRs]) and social contingency (parasocial interactions, e.g., math talk). In three studies (data collected in the DC area: 12/2015–10/2017), children's parasocial relationships and math talk with the intelligent character predicted quicker, more accurate math responses during virtual game play. Children performed better on a math transfer task with physical objects when exposed to an embodied character (Study 2), and when the character used socially contingent replies, which was mediated by math talk (Study 3). Results suggest that children's parasocial relationships and parasocial interactions with intelligent characters provide new frontiers for 21st century learning.